Integrasi Sekolah Kedalam Sistem Pendidikan Pesantren - Nurhadi (Tarbiyah Departement collaboration with AMCA, 2016)
The process of education in general, and the process of planting the values ​​of character in particular, is heavily influenced by environmental factors both inside and outside the school. Environmental conditions also determine the quality of the product (output) of the educational process. This is less recognized by the public, so that in case the phenomenon of delinquency, they menunding teachers of subjects such as manners of Religion teacher, teacher Pancasila and Citizenship Education and Counseling did not really instill character values. Thus the solution can be done to tackle the crisis mentioned above is to create conditions conducive environment by integrating the school into a boarding school education system, thus forming an educational and religious environment. The crisis in education today, emerged due to several factors, including: First, the historical factor where the Dutch colonialists always take discriminatory policies. Second, secular life orientation factors as the influence of western education concept. Third, the absence of factors that manages intellectual intelligence learning/intellectual quotient, emotional intelligence/ Emotional Quotient, and spiritual intelligence/Spiritual Quotient a balanced way, we are more directed to the education process of academic intelligence/intellect that is not oriented on solving program. Fourth, the environmental conditions are less instructive (in a school environment, namely: school culture, attitude and behavior of speech citizens of the school).